Kualitas Laporan Keuangan Sebelum dan Sesudah Penerapan Aplikasi MYOB pada UD Keluarga di Kota Payakumbuh - Deni saputra; Putri Intan Permata Sari; Agam Mei Yudha (Universitas Batanghari Jambi, 2021)
This study aims to determine whether the MYOB application can be used as a tool for recording financial statements effectively and efficiently at UD. Family in Payakumbuh. Jenis data used are primary data and secondary data. Method of data analysis conducted in this research is descriptive qualitative analysis and comparative analysis. The results of this study show that with the existence of computer-based accounting system, especially MYOB is very helpful business management, because the report produced more up to date and MYOB can improve the quality of financial statement information with speed, accuracy, completeness, etc. can clearly analyze each transaction there every day. The author suggests to UD. Family, to record all transactions that occur into MYOB so that it can further increase security in data storage and need training in order to run MYOB and be in accordance with accounting principles so that they can compile financial reports in a timely manner and can retrieve information quickly.